2022
DOI: 10.1002/anie.202214988
|View full text |Cite
|
Sign up to set email alerts
|

Decorating Single‐Atomic Mn Sites with FeMn Clusters to Boost Oxygen Reduction Reaction

Abstract: The regulation of electron distribution of single-atomic metal sites by atomic clusters is an effective strategy to boost their intrinsic activity of oxygen reduction reaction (ORR). Herein we report the construction of single-atomic Mn sites decorated with atomic clusters by an innovative combination of post-adsorption and secondary pyrolysis. The X-ray absorption spectroscopy confirms the formation of Mn sites via Mn-N 4 coordination bonding to FeMn atomic clusters (FeMn ac /Mn-N 4 C), which has been demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 52 publications
1
44
0
Order By: Relevance
“…To create high-efficiency air batteries, it is crucial to decrease excess potential of OER and ORR. [326][327][328][329][330] The inclusion of catalysts to the electrode has…”
Section: Metal-air Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…To create high-efficiency air batteries, it is crucial to decrease excess potential of OER and ORR. [326][327][328][329][330] The inclusion of catalysts to the electrode has…”
Section: Metal-air Batteriesmentioning
confidence: 99%
“…During the process of charging‐discharging, there is a significant over‐potential that leads to a loss of energy and a poor coulomb efficiency. To create high‐efficiency air batteries, it is crucial to decrease excess potential of OER and ORR [326–330] . The inclusion of catalysts to the electrode has been proved in various studies with the aim of successfully lowering the charge–discharge over‐potential of metal air batteries.…”
Section: Application Of G‐c3n4mentioning
confidence: 99%
“…18 Liu et al demonstrated that FeMn atomic clusters bonding to MnN 4 sites (FeMn ac /Mn–N 4 C) are conducive to the adsorption of O 2 during the ORR process. 19 Zhang et al revealed both the Co clusters and Co SAs of the Co 40 SAs/AC@NG electrocatalyst acted as active centers synergistically contributing to the ORR performance. 20 Although ORR performance has been significantly improved, there are still challenges in how to control the coexistence of metal clusters and single atoms in the preparation process.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that MN x sites are the main active sites for ORR, and the presence of metal nanoparticles (M-NPs) should be avoided for exposing maximally these active sites . Although some reports suggest that M-NPs encapsulated into few graphene layers can synergistically enhance the ORR. Introducing adjacent metal centers, either in the form of MN x or M-NP, can modulate the electronic structure of M–N–C sites and expedite the ORR kinetics. However, most of the reported studies are on the combination of SACs and M-NPs with the same metal types, and there are very rare reports which signify the synergistic coupling between SACs and M-NPs of different metal centers. This might be because of difficulty in achieving such active composite sites.…”
Section: Introductionmentioning
confidence: 99%